Analisis Penentuan Asal Usul Anak dari Perkahwinan Tidak Berdaftar (Kajian Kes Keputusan Nombor: 163/Pdt.P/2021/PA.TPI) - Jacky Candra Tirawang; Aris Bintania; M. Arbisora Angkat; Rizki Pradana Hidayatulah (Advances in Humanities and Contemporary Studies, 2025)
In the decision of case number: 163/Pdt.P/2021/PA.TPI, the judge granted the petition for the determination of the child’s origin from a marriage conducted under Islamic law (marriage siri). Meanwhile, Article 42 of Law Number 1 of 1974 concerning Marriage (Marriage Law) defines a legitimate child as a child born within or as a result of a lawful marriage. The purpose of this research is to understand the basis for the judge’s decision to grant the petition for the determination of the child’s origin from a marriage under Islamic law, so that it can later be determined whether the judge’s decision aligns with both Islamic law and positive law. The research method used is Library Research. The primary data source used is the attached decision of case number: 163/Pdt.P/2021/PA.TPI regarding the determination of the child’s origin from a marriage conducted under Islamic law (marriage siri). The data collection method used is documentation. The data analysis method employs descriptive analysis based on the theories of nasab (lineage), child origin, and marriage siri. The results of this study show that the judge decided that the marriage conducted by the petitioner was valid under Islamic law, as it met the requirements and conditions of marriage according to Islamic law. In deciding to determine the origin of the child, the panel of judges considered the legal, philosophical, sociological, empirical, and psychological aspects as the main considerations in determining that the child in question was a legitimate child. The determination of the child’s origin from the marriage under Islamic law in this case is considered valid under both Islamic law and positive law. The validation of the child’s origin in Islamic law is a necessity, as stated in the Quran, Surah Al-Furqan, verse 54. In positive law, the validation of the child in this case complies with the provisions outlined in Articles 55, paragraphs 1, 2, and 3 of Law Number 1 of 1974 and the Compilation of Islamic Law (KHI), particularly in Articles 103, paragraphs 1, 2, and 3, which address the validation of a child’s origin.